2020
DOI: 10.1371/journal.pone.0226235
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of a glycosyl hydrolase and cellular reprogramming enable Zymomonas mobilis growth on cellobiose

Abstract: Plant-derived fuels and chemicals from renewable biomass have significant potential to replace reliance on petroleum and improve global carbon balance. However, plant biomass contains significant fractions of oligosaccharides that are not usable natively by many industrial microorganisms, including Escherichia coli , Saccharomyces cerevisiae , and Zymomonas mobilis . Even after chemical or enzymatic hydrolysis, some carbohydrate remains as no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…mobilis AX101 that recombinantly expresses the arabinose and xylose utilization gene cascade 53 . To increase the substrate availability, heterologous expression of glycosyl hydrolases from Cellvibrio japonicus Cel3A and Caulobacter crescentus CC_0968 enabled Z. mobilis to use cellobiose for ethanol production 54 . As Z. mobilis uses the Entner Doudoroff pathway, producing only one ATP, it raises concern over cellular health if multiple genes are expressed at once.…”
Section: Whole‐cell Biocatalysis: Changing Paradigm Of Biorefineriesmentioning
confidence: 99%
See 1 more Smart Citation
“…mobilis AX101 that recombinantly expresses the arabinose and xylose utilization gene cascade 53 . To increase the substrate availability, heterologous expression of glycosyl hydrolases from Cellvibrio japonicus Cel3A and Caulobacter crescentus CC_0968 enabled Z. mobilis to use cellobiose for ethanol production 54 . As Z. mobilis uses the Entner Doudoroff pathway, producing only one ATP, it raises concern over cellular health if multiple genes are expressed at once.…”
Section: Whole‐cell Biocatalysis: Changing Paradigm Of Biorefineriesmentioning
confidence: 99%
“…53 To increase the substrate availability, heterologous expression of glycosyl hydrolases from Cellvibrio japonicus Cel3A and Caulobacter crescentus CC_0968 enabled Z. mobilis to use cellobiose for ethanol production. 54 As Z. mobilis uses the Entner Doudoroff pathway, producing only one ATP, it raises concern over cellular health if multiple genes are expressed at once. Thus, it is essential to introduce pathways that can satisfy the needs independently with minimal or no effect on cellular viability.…”
Section: Bioethanol: the Regular Optionmentioning
confidence: 99%
“…However, these studies only demonstrated lignocellulosic materials conversion in resting cells. In order to overcome this issue, Kurumbang et al ( 2020 ) proposed the heterologous expression and secretion of a glycosyl hydrolase (GH) β-glucosidase from Caulobacter crescentus in Z. mobilis , that enables an efficient conversion of oligosaccharides. The engineered strain was further subjected to an adaptation in cellobiose medium, and growth on cellobiose was achieved.…”
Section: Use Of Alternative Substrates and Feedstockmentioning
confidence: 99%